PEMAHAMAN KEBERAGAMAAN DAN GERAKAN KELOMPOK FPI SURABAYA - Ma’arif, Syamsul (TEOLOGIA, 2012)
Abstract: Attitudes of FPI (Islamic Defenders Front) in Indonesia so far Â impressed frontal and against any form of indecent behavior. Their action, in fact it can be said as one of the deepest expression of a group of Muslims in articulating religious teachings are embraced, or as an attitude of "piety" in viewing of all the different faiths in the belief that he believes. Especially in view of problems that are clearly regarded as a form of disobedience, apostasy and blasphemy. The responses and reactions, as well as research that has been conducted by the author in Surabaya is in order to uphold the principles of faith are considered "correct" earlier. This paper aims to provide comprehensive information on what factors underlie the birth of contemporary religious groups-particularly FPI in Surabaya. And find the religious understanding, activity and movements FPI group in the area. Overview of the results of this study are expected to eventually be able to eliminate the possibility of misunderstanding information is the cause of the onset of prejudice and stereotypes is the first step in conflict or resolve conflicts between religious communities in a comprehensive manner. Therefore, the known diversity of religious groups with the dynamics of movements will make it easier for religious communities to learn from each other. Abstrak: Sikap-sikap FPI (Front Pembela Islam) di Indonesia selama ini terkesan âfrontalâ dan melawan setiap bentuk kemunkaran. Aksi mereka, sebenarnya bisa dikatakan sebagai salah satu bentuk ekspresi terdalam dari sekelompok orang muslim dalam mengartikulasikan ajaran-ajaran agama yang dipeluknya, atau sebagai bentuk sikap âkesalehanâ dalam memandang setiap keyakinan yang berbeda dengan keyakinan yang diyakininya. Apalagi dalam memandang persoalan yang jelas-jelas dianggap sebagai bentuk kemaksiatan, kesesatan dan penodaan agama. Maka respons dan reaksi mereka, sebagaimana hasil penelitian yang telah dilakukan penulis di Surabaya adalah dalam rangka menegakkan prinsip keimanan yang dianggap âbenarâ tadi. Tulisan ini bertujuan untuk memberikan informasi yang komprehensif tentang faktor apa saja yang melatari lahirnya kelompok-kelompok keagamaan kontemporerâterutama sekali FPI di Surabaya. Sekaligus mengetahui pemahaman keagamaan, aktifitas dan gerakan-gerakan kelompok FPI di daerah tersebut. Gambaran hasil penelitian ini pada akhirnya diharapkan mampu mengeliminasi kemungkinan kesalahpahaman informasi yang menjadi sebab timbulnya prejudice, dan stereotype yang merupakan langkah awal terjadinya konflik atau mengatasi konflik antar komunitas agama secara komprehensif. Sebab, dengan diketahui keanekaragaman kelompok-kelompok keagamaan dengan dinamika gerakannyaÂ  akan lebih memudahkan masyarakat agama untuk saling belajar satu sama lain. Keywords: Pemahaman Keberagamaan,Â  Gerakan, FPI Surabaya, liberalisme, NU, Muhammadiyah.